AVALIAÇÃO DE DANOS NO DNA EM TRABALHADORES RURAIS - Goettems, Pauline B.; Santos, Greice F. F. d.; Bandeira, Camila d. S.; Bellinaso, Maria d. L.; Vieira, Carolina P.; Rocha, João B. d. (Salão do Conhecimento, 2013)
Resumo